Fluid mechanics and fluid power engineering - Kumar, D.S (S.K. Kataria & Sons, 2008)
Basic concepts of fluids and fluid flow are essential in all engineering disciplines to get better understanding of the courses in the professional programmes, and obviously its importance as a core subject need not be overemphasised.